ANALISA KETAHANAN DAN KINERJA PANEL SURYA DI KAWASAN PESISIR - Ain Sahara; Bambang Sugeng; M Saleh (Sekolah Tinggi Teknologi MIGAS, 2022)
The coastal area is an area that is high in salt content so that it can corrode the tools around it. As with solar panels in Solar Power Plants if installed in coastal areas, their performance will likely decrease. Although Solar Power Plants is a renewable energy that is obtained free of charge from sunlight, the solar panel attached to Solar Power Plants is also a tool or instrument which functions to create electric power. The hypothesis that has been made is that solar panels have a decreased performance when in coastal areas compared to solar panels installed in urban areas. In this study, a comparison or analysis of the performance of solar panels in coastal areas with urban areas will be discussed. Therefore, from this analysis, it is hoped that it can draw a conclusion that there is special or extra care when installing Solar Power Plants in coastal areas.